Analysing the social perception of the WSL Portugal Pro as a surf tourism catalyst for Peniche - Diego Santos González (Discover Sustainability)
Abstract This study addresses how surfing events, exemplified by the WSL Portugal Pro, act as catalysts for tourism and foster socio-economic and cultural transformations in Peniche, a former fishing village in Portugal that has emerged as a renowned surf destination. Utilizing a mixed-methods approach, including semistructured interviews, life stories, and autoethnography, the research examines perceptions of tourism growth, economic benefits, social challenges, and changes in Peniche’s image. The findings reveal a significant increase in surf tourism directly linked to the competition, which has revitalized the local economy but also brought concerns about overcrowding and cultural identity loss. Nevertheless, these challenges present opportunities to implement effective tourism management strategies that balance economic benefits with social and environmental sustainability. Integrating Peniche’s historical narrative into the tourist experience and managing visitor capacity are essential for maintaining both the community’s quality of life and the destination’s appeal. By providing a comprehensive understanding of Peniche’s transformation, this study offers valuable insights for future research and policy development in sustainably managing surf tourism.